Analysis of Adhesive Wear Behaviour of Cu-10Sn-4Si Composite Reinforced with SiC particles Using Optimization Technique. (2020) - Ankit, A.V.; Krishna Kumar, R.; Radhika, N.
Abstract: Cu-10Sn-4Si reinforced with 10 wt. % SiC was synthesized using stir casting technique and cylindrical specimens of diameter 20 mm and length 150 mm were obtained.Dry sliding wear behavior of copper composite was analyzed by performing experiments using pin-on-disc tribometer. Taguchi's method was utilized for designing the number of experiments using L16 orthogonal arrayfor investigating the wear behavior. Three factors and four level design was selected namely Load (15N, 25N, 35N, 45N), Velocity (1.5m/s, 2.5m/s, 3.5m/s, 4.5m/s) and Distance (500m, 1000m, 1500m, 2000m).Optimization of parameters was done using the Signal-to-Noise ratio. Analysis of Variance results revealed that load had the most impact on wear rate followed by sliding velocity and distance. The regression equation was developed and validated with confirmation experiment. X-ray diffraction analysis was conducted on the worn specimen to find out phase formations. Scanning Electron Microscopy analysis were performed on the surface of worn specimens and found that more delamination occurred at a load of 45 N